Separation of yeasts by addition of flocculent cells of Saccharomyces cerevisiae - Mortier, Annelies (2007)
Separation of yeast cells using a co-flocculation process was investigated. Co-flocculation is a fast process (within few minutes), occurs in a broad pH range (3.0–8.0) and requires a small amount of calcium (0.1 mM). Agitation affects yeast aggregation; however, an agitation between 60 rev/min and 160 rev/min has only a little influence on the co-flocculation process. The ratio flocculent/ non-flocculent cells that induced the settling of 50 and 90% of the cells of S. cerevisiae was 1:7 and 1:1, respectively. Separation of non-flocculent cells can be carried out at any time of the growth cycle. No difference in the efficiency of co-flocculation carried out in buffer (pH 4.0 with 10 mM calcium) or in 48 h-fermented broth was observed. Flocculent cells of Saccharomyces cerevisiae had the ability to sediment non-flocculent cells of S. cerevisiae and Kluyveromyces marxianus, which shows the suitability of the co-flocculation process for separation of different kinds of non-flocculent cells.